Regional Economic Development through Halal Tourism: An Entrepreneurship Model Based on Local Wisdom - Husnurrosyidah Husnurrosyidah; Arya Andi Irawan; Amin Kuncoro (Global Health Science Group, 2025)
In the context of the rapid global growth of the halal tourism industry, this study examines the role of halal tourism in fostering regional economic development in Pati Regency, Central Java, Indonesia. The research focuses on two prominent spiritual tourism sites: the Tomb of Sheikh Ahmad Mutamakkin in Kajen and the Tomb of Sheikh Ronggo Kusumo, which serve as significant pilgrimage destinations rooted in Islamic heritage. This qualitative field study employs in-depth interviews with key informants including officials from the Pati Regency Youth, Sports and Tourism Office and Trade Office, tomb caretakers, village government representatives and local traders supplemented by secondary data sources. Findings reveal that the presence of these halal tourism destinations has significantly enhanced local economic activity through increased trade, service provision and micro, small and medium enterprise (MSME) development. Both sites comply with the Global Muslim Travel Index (GMTI) halal tourism criteria including the provision of Muslim-friendly facilities, halal food availability and cultural preservation. Furthermore, the study identifies a distinct local wisdom-based entrepreneurship model practiced by traders around these sites, characterized by values such as religiosity, honesty, discipline, hard work, creativity, innovation, independence, responsibility, cooperation, leadership, perseverance, risk-taking propensity, commitment, realism, curiosity, effective communication, strong achievement motivation, generosity and action orientation. The integration of local wisdom into entrepreneurial practices emerges as an effective and sustainable strategy for developing inclusive halal tourism, thereby contributing to regional economic growth and community welfare in Pati Regency.